Conservation status of the dhole Cuon alpinus in north-east India, with a focus on Dampa Tiger Reserve, Mizoram - Singh, P; Srivathsa, A; Macdonald, DW (Cambridge University Press, 2019)
Despite the efforts invested in their conservation, the status of many threatened carnivores in key conservation landscapes remains unknown. The dhole Cuon alpinus is an Endangered social carnivore whose geographical range has contracted by c. 80% since the early 20th century. North-east India is a critical link between South Asian and South-east Asian dhole populations. In this study we compiled presence records of dholes across north-east India, from multiple sources. We also conducted camera-trap surveys in one part of this region, Dampa Tiger Reserve in the state of Mizoram. We examined the influence of ecological and management factors on fine-scale site-use by dholes in Dampa Tiger Reserve, showing a positive association of dhole site-use with sambar Rusa unicolor encounters, distance to the forest boundary and presence of forest department personnel, underscoring the importance of prey and protection. Our findings also highlight the need for targeted, multi-scale assessments of dhole ecology across other sites in north-east India.